Panorama of health marketing in Latin America - Nery Suárez-Lugo (Horizonte Sanitario, 2017)
The complexity of health problems, both in origin and cause, as well as in the way of solving them, leads to the need for a holistic approach for analysis, in which various medical and social sciences are intertwined to fulfill the task of achieve well-being in the population. The transition from the biological to the social approach in health leads to a change in the way of thinking and acting, to which the marketing approach can contribute as a strategy to facilitate such a process. Marketing applied to health Marketing in its social approach, is governed by ethical principles and has a wide range of application to health. It is a tool for health activity, which by appropriating it, allows bringing to the market medicines, medical instruments and technologies with a rational approach, offering and reorienting services, reconciling the objectives and purposes of the institution with those of the patient-user, to achieve both ends. Its effectiveness in changing the behavior of the population that is required to achieve its well-being has been demonstrated and has a wide range of application in promoting health and promoting healthy lifestyles, designing and implementing health programs. The business management of health management with the application of marketing in both services and programs, does not mean in any way to market it, nor is this the approach advocated, but to offer a public health with total accessibility, optimizing resources in order to adequately serve all the population that requires it. In its social approach as a tool, marketing has been growing in recent years worldwide, because of its contribution to solve the different public health problems that are generated and tends to increase its incorporation in different fields of human endeavor 1, 2, 3.